Bromine-induced facile synthesis of butenolides and spirobutenolides from sterically congested tetrasubstituted dialkyl alkylidene succinates - Patel, Ramesh M.; N. P. Argade (Synthesis-Stuttgart, 2010)
Starting from sterically congested tetrasubstituted dialkyl alkylidene succinates, facile general approach to several dialkyl substituted butenolides and spirobutenolides with the generation of quaternary carbon center has been demonstrated via bromine-induced dealkylative regioselective intramolecular cyclization and dehydrobromination pathway. The mechanistic aspects involved in the formation of butenolides have been also described in brief.
Keywords: alkylidene succinates; bromine; butenolides; intramolecular cyclizations; spirobutenolides